The effect of various polyelectrolytes on alcohol oxidase/horseradish peroxidase/ferrocene modified carbon paste electrodes - Larsson, Niklas; Gorton, Lo (My University, 1997)
Two enzyme based alcohol biosensors were constructed by co-immobilizing alcohol oxidase and horseradish peroxidase into a carbon paste matrix. The effects of chemically modifying HRP, adding a mediator and different polyelectrolytes were examined, aiming at better operational stability when used in a flow injection system. The electrodes are characterized (sensitivity, detection limit, operational stability) when operated at an applied working potential of −50 mV vs. Ag/AgCl.